A sensitive and high‐speed traveling wave protection scheme for HVDC transmission line. (20th December 2013) - Min, Xu; Zexiang, Cai; Kunlun, Han; Yongjun, Zhang
Summary This paper presents a novel traveling wave protection scheme to satisfy the sensitive and high‐speed performances of protective relaying for line commutated converter high voltage direct current (HVDC) transmission lines. The scheme performs by using a startup and two auxiliary criteria with a small sampling interval to ensure the sensitivity of fault detection: the startup criterion adopts the concept of voltage derivative to distinguish between internal and external faults; the two novel auxiliary criteria adopt concepts of voltage difference and voltage ratio to deal with noise interference, which is brought to the fore by using small sampling interval. Besides high sensitivity, the scheme is able to achieve an excellent high‐speed performance because it acts only on the basis of the first waveform following a fault. Simulation studies have been conducted in power systems computer aided design/electromagnetic transients including direct current (PSCAD/EMTDC) to evaluate the scheme, which shows that the scheme permits both high speed and high sensitivity for direct current line fault detection at a satisfactory level. Copyright © 2013 John Wiley & Sons, Ltd.